OPHIOLITE-BEARING VERMOSHI FLYSCH (ALBANIAN ALPS, NORTHERN ALBANIA): ELEMENTS FOR ITS CORRELATION IN THE FRAME OF DINARIC-HELLENIC BELT - Marroni, Michele; Pandolfi, Luca; Onuzi, Kujtim; Palandri, Silvia; Xhomo, Abedin (Ofioliti, 2009)
The tectonic setting of the Albanian Alps, Northern Albania, is characterized by a thick pile of tectonic units whose uppermost structural level is represented by the Vermoshi Unit, cropping out just few km north of the Shkoder-Péc Line. This unit includes a single formation, the Vermoshi Flysch, characterized by turbidite deposits consisting of arenites, shales and marls. The Vermoshi Flysch has been sampled for paleontological datings and petrographical analyses of the arenite beds along five selected and well exposed sections in the Vermoshi Valley. The nannoplancton and forams associations detected in the analyzed samples point out to a Barremian age, whereas the petrographical modal analysis of arenites indicates that all the samples have a mixed/hybrid silicilastic- carbonate composition, ranging from quartz-rich sublitharenites to quartz-poor litharenites. However, the main feature ot these arenites is the occurrence of fragments derived from an ophiolite sequence. The petrographical data suggest that these deposits can be regarded as supplied by two different source areas, represented by the margins of the basin where the Vermoshi Flysch was deposited. Whereas one of the border was represented by the Adria continental margin, the opposite one was characterized by an advancing nappe, constituted by ophiolites and their sedimentary cover. In this frame, the Vermoshi Flysch can be regarded as the southernmost part of the Vranduk Flysch, cropping out in Serbia and Croatia. This type of deposits, widespread in the Dinaric-Hellenic belt, can be considered as the sedimentary marker of the Late Jurassic - Early Cretaceous tectonic phases related to the closure of the oceanic area present between the Adria and the Eurasia plates.